Um estudo sobre o atendimento em creches às crianças com deficiência ou transtorno do desenvolvimento: o que dizem familiares e profissionais de um município paulista - Diniz, Nathalia Lucena [UNIFESP] (2016)
This dissertation?s theme is the educational inclusion of little children with disability or disorders. The aim is, through semi-structured interviews answered by relatives and professionals from daycares within a municipality of Sao Paulo, to understand and discuss conceptions about child development, disability and disorders, educational inclusion and the role of daycares, involved in the process to assist these children. The research has as its methodological and theoretical foundation in cultural-historical psychology, with highlight to contributions from Lev Vygotsky on the social character ? mediated ? of human constitution and the role of others and of the language on the cultural development of children with disability. It was also considered contributions of Brazilian researchers about children education and special education, in an inclusive perspective, and documents conducting these educational genre and the specific legislation. The work consists in a case study through qualitative approach. The analysis points towards the importance of educational inclusion on school in these children?s lives and to the changes evoked by their presence in the regular school system. The roles played by relatives and professionals conceptions about the child development, disability, disorders and educational inclusion are emphasized. This work discusses a context which reflects the current changes taking place regard little children?s education and special education.